2010
DOI: 10.5194/os-6-285-2010
|View full text |Cite
|
Sign up to set email alerts
|

On contribution of horizontal and intra-layer convection to the formation of the Baltic Sea cold intermediate layer

Abstract: Abstract. Seasonal cascades down the coastal slopes and intra-layer convection are considered as the two additional mechanisms contributing to the Baltic Sea cold intermediate layer (CIL) formation along with conventional seasonal vertical mixing. Field measurements are presented, reporting for the first time the possibility of denser water formation and cascading from the Baltic Sea underwater slopes, which take place under fall and winter cooling conditions and deliver waters into intermediate layer of salin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…It has been shown by a modelling study that mesoscale processes are dominant dynamical features of the Gulf, especially in its coastal zone (Laanemets et al, 2011). Thus, mesoscale eddies and fronts with characteristic horizontal scale determined by the internal Rossby radius (Alenius et al, 2003) create corresponding horizontal variability of vertical stratification, as has been documented by repeated across-Gulf surveys (e.g. Lips et al, 2010).…”
Section: T Liblik and U Lips: Synoptic-scale Quasi-stationary Thermmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been shown by a modelling study that mesoscale processes are dominant dynamical features of the Gulf, especially in its coastal zone (Laanemets et al, 2011). Thus, mesoscale eddies and fronts with characteristic horizontal scale determined by the internal Rossby radius (Alenius et al, 2003) create corresponding horizontal variability of vertical stratification, as has been documented by repeated across-Gulf surveys (e.g. Lips et al, 2010).…”
Section: T Liblik and U Lips: Synoptic-scale Quasi-stationary Thermmentioning
confidence: 86%
“…Baltic Sea index in January-February, although it has been shown that denser surface waters sinking from shallow areas during autumn and spring can also influence CIL temperature the following summer (Chubarenko and Demchenko, 2010). Salinity increase in the deep layer observed after the mid1990s was suggested to be mostly caused by a major inflow of North Sea waters into the Baltic Sea in 1993.…”
Section: T Liblik and U Lips: Synoptic-scale Quasi-stationary Thermmentioning
confidence: 99%
“…Cold intermediate layers (CILs) are common summer feature of many subarctic coastal seas. Such water masses are found for example in the Black Sea [ Tuzhilkin , 2008], the Baltic Sea [ Chubarenko and Demchenko , 2010], the Bering Sea [ Kostianoy et al , 2004] the Sea of Okhotsk [ Rogashev et al , 2000], the Gulf of St. Lawrence [ Banks , 1966] and can also be found in coastal oceans [ Petrie et al , 1988]. At formation, CILs may represent up to 45% of the total water volume of those systems [e.g., Galbraith , 2006] and therefore largely control the state and climate of subarctic coastal systems as well as the marine ecology [ Ottersen et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The CIL is formed when this surface mixed layer becomes insulated from the atmosphere by near‐surface stratification caused by sea‐ice melt, heat fluxes and increase runoff at the onset of spring. Other mechanisms such as horizontal/intra‐layer convection may also contribute to CIL formation [ Chubarenko and Demchenko , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…For such waters, the situation is transitory. Surface water freezing begins at (weak but) stable thermal stratification (similar to lakes), but with the initiation of the ice formation, the rejection of brine easily overcomes the stabilizing effect of thermal stratification, since the contribution of temperature to the variations of water density is known to be small compared to the influence of water salinity in the Baltic Sea Demchenko, 2010, Chubarenko andStepanova, 2018). Taking into account severe wind/wave conditions at mid-latitudes, vertical mixing of the water column can be assumed as the background process for the incorporation of MPs into ice both before and after the beginning of freezing.…”
Section: Mixing Regime Of Underlying Watermentioning
confidence: 99%